Ultrasonographic assessment of the renal size using a kidney length to vertebral body length ratio in cats - Martinez, Miryam; Soler, Marta; Laredo, Francisco G.; Belda, Eliseo; Agut, Amalia (Frontiers in Veterinary Science, 2022)
Ultrasonographic assessment of the renal size can provide useful clinical information, in combination with other ultrasonographic parameters. The aims of this study were to establish the agreement between the ultrasonographic and radiographic measurements of the kidneys (K) and vertebral bodies (L5 and L6), second to establish an ultrasonographic measurement of kidney-to-vertebral body (L5 and L6) ratio to estimate the renal size in cats, and to assess the impact of age, body weight, sex and gonadal status on the ultrasonographic measurements of the kidneys, vertebral bodies and ratios. The vertebral bodies of L5 and L6 were chosen as they were easy to identify with US using the lumbosacral junction as a landmark, and they are not usually affected by vertebral anomalies. Sixty cats (19 intact males, 12 neutered males, 17 intact females, and 12 neutered females) were included in the study. The cats were divided into three age groups (<7months, 7 months-7 years, and >7years), two body weight categories (<3.5 kg and >3.5 kg), and two sex and gonadal status groups (male and female, and intact and neutered respectively). Measurements of the renal and vertebral body length were performed on the radiographic and ultrasonographic images. Two different ratios were obtained K/L5 and K/L6. There was not significant difference between the length of both kidneys and the vertebral bodies length of L5 and L6 on ultrasonographic or radiographic images. There was a good agreement between ultrasonographic and radiographic measurements of both kidneys and vertebral bodies. In conclusion, the kidney length to L6 length ratio obtained: 1.81 ± 0.20 (1.76-1.86) is a useful and practical method for evaluating the size of the feline kidney and was not influenced by the age, body weight, sex or gonadal status.